Efeito do farnesol sobre fatores de virulência de Candida albicans e Streptococcus mutans - Fernandes, Renan Aparecido [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the activity of a quorum sensing molecule, farnesol, in biofilm formation of Candida albicans ATCC 10231 and Streptococcus mutans ATCC 25175. Initially farnesol was diluted in methanol and then in artificial saliva (AS). Minimum inhibitory concentration tests (MIC) of farnesol against Candida albicans ATCC 10231 cells and Streptococcus mutans ATCC 25175 suspension were based on the microdilution method. Farnesol was prepared at concentrations of 1.56, 3.125, 6.25, 12.5, 25, 50, 70, 150 and 300 mM, and placed in contact with biofilms in formation of Candida albicans and Streptococcus mutans for 48 hours. Its antibiofilm activity was determined by quantifying the total biomass (stained with crystal violet (CV)), enumeration of colony forming units (CFUs) and metabolic activity (XTT). It was further carried out a cell death time curve for both microorganisms studied. After the treatment with farnesol, the matrix of the biofilm was extracted and analyzed in terms of protein and carbohydrates, in addition to the pH test for S. mutans and examination of enzymatic activities of proteinase, fosfolipase and hemolytic for Candida albicans. The structure of biofilms was analyzed by scanning electron microscopy. The MIC values were 150 mM for C. albicans and 6.25 mM for S. mutans. Farnesol decreased the formation of single and mixed biofilms, with significant reductions of 37-90% and 64-96% respectively for the total biomass and metabolic activity. For single biofilms, farnesol concentrations equal to or higher than 3.125 mM promoted significant reductions (1,3-4,2log10; p <0.05) in the CFU for single biofilms, while in mixed biofilms the reductions (0,67-5,32log10; p <0.05) were noted at concentrations of 1.56 mM. For cell death curve after an hour in contact with those microorganisms, farnesol reduced 1 log10...

O objetivo deste estudo foi avaliar a atividade da molécula de quorum sensing farnesol na formação de biofilmes simples e misto de Candida albicans ATCC 10231 e Streptococcus mutans ATCC 25175. Inicialmente o farnesol foi diluído em metanol e posteriormente em saliva artificial (SA). Os testes de concentração inibitória mínima (CIM) do farnesol contra as células de Candida albicans ATCC 10231 e Streptococcus mutans ATCC 25175 em suspensão foram baseados no método da microdiluição. O farnesol diluído nas concentrações de 1,56, 3,125, 6,25, 12,5, 25, 50, 70, 150 e 300 mM foi aplicado sobre os biofilmes de Candida albicans e Streptococcus mutans (formação) e após 48 horas de contato sua atividade antibiofilme foi determinada por meio da quantificação da biomassa total (coloração com violeta cristal (CV)), enumeração das unidades formadoras de colônias (UFCs) e atividade metabólica (XTT). Foi ainda realizada uma curva de tempo de morte celular para os dois microrganismos estudados. Após o tratamento com o farnesol, a matriz dos biofilmes foi extraída e analisada em termos de concentração de proteínas e carboidratos, além do teste de pH para S. mutans e verificação das atividades enzimáticas de proteinase, fosfolipase e hemolítica para Candida albicans, ainda a estrutura dos biofilmes foi analisada por meio da microscopia eletrônica de varredura. Os resultados de CIM foram de 150 mM para C. albicans e de 6.25 mM para S. mutans. O farnesol diminuiu a formação de biofilmes simples e mistos, com reduções significativas de 37-90% e 64-96%, respectivamente para a biomassa total e atividade metabólica. Para os biofilmes simples, concentrações de farnesol iguais ou maiores que 3,125 mM promoveram reduções significativas (1,3-4,2 log10; p < 0,05) nas UFCs, enquanto que para os biofilmes mistos reduções...
Keywords: Biofilme; Candida albicans; Streptococcus mutans; Farneseno álcool; Fatores de virulência; Biofilms